2008
DOI: 10.1634/theoncologist.2008-0133
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Practicing on the Tip of an Information Iceberg? Evidence of Underpublication of Registered Clinical Trials in Oncology

Abstract: Objective. Members of the International Committee of Medical Journal Editors require, as a condition of consideration for publication, that all clinical trials be registered in a public trials registry. We evaluated the proportion of registered trials that are published in the peer-reviewed literature.Methods. After downloading the contents of the National Institutes of Health's ClinicalTrials.gov registry, we used key words to identify trials in oncology. We then evaluated the proportion of trials that had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 17 publications
0
44
1
1
Order By: Relevance
“…Ramsey and Scoggins identified 2028 completed or terminated cancer trials from NIH's ClinicalTrials.gov registry in September 2007. 391 They then searched ClinicalTrials.gov and PubMed for peer-reviewed publications of these trials. It was found that only 19.5% of the 1791 completed cancer trials and 3.4% of the 237 terminated trials had been published in peer-reviewed journals.…”
Section: Prospective Registration Of Trialsmentioning
confidence: 99%
“…Ramsey and Scoggins identified 2028 completed or terminated cancer trials from NIH's ClinicalTrials.gov registry in September 2007. 391 They then searched ClinicalTrials.gov and PubMed for peer-reviewed publications of these trials. It was found that only 19.5% of the 1791 completed cancer trials and 3.4% of the 237 terminated trials had been published in peer-reviewed journals.…”
Section: Prospective Registration Of Trialsmentioning
confidence: 99%
“…It is increasingly difficult for medical oncologists to keep current with the generally incremental advances published regularly by well-known and well-respected medical journals. And yet, as Ramsey and Scoggins point out in this edition of The Oncologist, we may be struggling to keep up with information that represents only "the tip of the iceberg" [3]. Slipping beneath the surface is a wealth of unpublished data that might prove valuable to the cancer research community.…”
mentioning
confidence: 99%
“…Ramsey and Scoggins hypothesize that a major reason for failure to publish is selection bias against trials that do not meet their endpoints and, indeed, the majority (57%-90%) of the published trials are positive [3]. But other factors aside from a negative result may defeat a trial and its publication.…”
mentioning
confidence: 99%
“…6 In that regard, Ramsey and Scoggins point out that journal reviewers may be disinterested in nonsignificant trial results that do not appear to change practice or produce new information. 14 Still, recent evidence suggests several troubling deficiencies in the information that is available to physicians making prescribing Processes that encourage transparent interplay between payers, manufacturers, providers and patients may also provide part of the solution. The DoD formulary review process, described in an article elsewhere in this issue, combines detailed and evidencebased economic and clinical review with qualitative assessments of provider and beneficiary opinion.…”
Section: Interpretations Of Current Evidence About Clinical Trial Mismentioning
confidence: 99%
“…When the sample was restricted to trials registered prior to September 2004, 21.0% of trials were published after more than 3 years of follow-up. 14 A fascinating look at the process that reportedly underlies selective publication was provided in a January 2009 report by Landefeld and Steinman, who were unpaid consultants for the plaintiff (biologist David Franklin) in a lawsuit over the manufacturer's promotional activities for the anticonvulsant gabapentin. 15 Based on a content analysis of corporate documents, which became publicly available as a result of the discovery process in the litigation, study authors reported extensive evidence of ghostwriting and a "publication strategy" for marketing purposes.…”
mentioning
confidence: 99%